Humans, saints, and earth beings: community through combination in a contemporary Nahua village of Northeastern Mexico - Ariel de Vidas, Anath, author; Davis, Pablo J., translator; University Press of Colorado, publisher (Colorado State University. Libraries, 2026)
Drawing on ethnographic work in the small Nahua village of La Esperanza in northeast Mexico, Ariel de Vidas explores how how La Esperanza maintains a collective culture grounded in a close connection with the earth while simultaneously being integrated into the modern world.--Provided by publisher.
Note on Phonemic Transcription of Northern Nahuatl -- Introduction: We Speak to the Tepas Because We Are Indigenous -- Exclusive Dichotomies -- In Search of the Local Ethnotheory of a Singular Ethic -- Approach -- 1. Where There's Life, There's Esperanza -- Introduction -- Agrarian and Political Organization -- Historical Background of the Village of La Esperanza and of the Agrarian Community of Santa Clara -- The Contemporary Scene -- Economic Activity -- "Pueblo chico, infierno grande"? -- 2. The Miracle of the Maize -- Introduction -- The History of the Miracle -- The Great Drought -- Origins of the Chikomexochitl Ritual -- Land, Territory, and Community -- 3/ The Three Layers -- Introduction -- The Domestic Altar: Point of Departure and Arrival -- The Tepas: Guardians of the Earth -- The Ritualists -- The Local Notion of Work -- The Ritualists' Promises -- The Three Moments of the Ritual -- 4. Fulfilling the Covenant -- Introduction -- Novena-Promise for the Family -- Offerings at the Beginning of the Year to the Means of Production -- Healings -- A Synergy Set in Motion -- 5. On Earth as It Is in Heaven -- Introduction -- Rites of Passage -- A Single Integrative Space: "Combinationism" -- 6. The Patronal Festival -- Introduction -- "All-Out Festival in La Esperanza" -- Festival Everlasting -- Ritual and Political Sociability -- 7. Flowers Are the Most Important Thing of All -- Introduction -- The Omnipresence of Flowers in the Ritual Life of La Esperanza -- Flowers in the Ancient Mesoamerican World -- The Marigold Flower -- Transitions-Transformations in the Christianized Mesoamerican World -- Flowers as Concatenators of the "Power" in "the Near and the Joined" -- The Work-Power-Flower Principle -- 8. The Earth Unites Us and Custom Brings Us Together -- Introduction -- El costumbre and Its Connection with the World Beyond the Community -- The Pastoral Indígena in La Esperanza -- Between Custom, Tradition, and Culture -- A Political History of El costumbre -- Conclusion The Tepas Are Bilingual.
This work was published in collaboration with the Société des Américanistes as part of its 2022 Prize and Publication Grant.
Keywords: Nahuas -- Mexico -- Tantoyuca -- Social life and customs; Nahuas -- Mexico -- Tantoyuca -- Rites and ceremonies; Esperanza (Tantoyuca, Veracruz-Llave, Mexico) -- Social life and customs; Esperanza (Tantoyuca, Veracruz-Llave, Mexico) -- History